Waste Refinery: The Valorization of Waste Plastics and End-of-Life Tires in Refinery Units. A Review - Palos, Roberto; Gutiérrez, Alazne; Vela, Francisco J; Olazar, Martin; Arandes, José M; Bilbao, Javier (Energy & fuels, 2021)
This review collects a wide range of initiatives and results that expose the potential of the refineries to be converted into waste refineries. Thus, they will use their current units for the valorization of consumer society wastes (waste plastics and end-of-life tires in particular) that are manufactured with petroleum derivatives. The capacity, technological development, and versatility of fluid catalytic cracking (FCC) and hydroprocessing units make them appropriate for achieving this goal. Polyolefinic plastics (polyethylene and polypropylene), the waxes obtained in their fast pyrolysis, and the tire pyrolysis oils can be cofed together with the current streams of the industrial units. Conventional refineries have the opportunity of operating as waste refineries cofeeding these alternative feeds and tailoring the properties of the fuels and raw materials produced to be adapted to commercial requirements within the oil economy frame. This strategy will contribute in a centralized and rational way to the recycling of the consumer society wastes on a large scale. Furthermore, the use of already existing and, especially, depreciated units for the production of fuels and raw materials (such as light olefins and aromatics) promotes the economy of the recycling process.